Effect of thiocyanate on shelf-life of milk - Ummuna, V.I.; Tessema, A. (MOA, 2000)
Milk produced by smallholders in sub-Saharan Africa is used in a number of ways but primarily to meet family needs and the needs of calves. Milk may be sold to neighbors and to consumers in nearby town or village. Milk excess of family requirements is usually processed into butter and cheese. Unhygienic milk production and processing condition result in inferior products with a short shelf-life milk and milk products that may be produced particularly during periods of maximum milk production will be spoiled, resulting in an economic loss to the smallholder. Butter preservation techniques will result in more milk being processed and in products of better quality and longer shelf-life. The experiment described was carried out to determine the feasibility of increasing the shelf-life of milk by chemical means and to investigate alternative preservation techniques. Accordingly the experimental result revealed that addition of thiocyanate extended the shelf-life of milk stored at different temperatures. The greater the amount of added thiocyanate and the lower the storage temperature the longer the shelf-life. In addition, the better the hygienic quality of the milk the better the effect of added thiocyanate. The experimental finding will demonstrate to smallholders and lager-scale milk producers and processors the possibilities and merits of the preservation method used.